Heavy-Duty Battery Electric Buses’ Integration in Cities Based on Superfast Charging Technologies: Impact on the Urban Life - Manuel Mathes (Sustainability, 2022)
As part of this work, several Battery Electric Buses (BEBs) of 9 m, 12 m, and 18 m lengths and superfast chargers based on a pantograph of up to 600 kW were developed and demonstrated in selected European cities. In Osnabrück (OSN), Germany, superfast charging technologies based on BEBs were demonstrated, and numerous measurement campaigns were conducted. Within the scope of this work, two measurement campaigns are presented, which are related to the impact of BEBs on the urban life, i.e., people’s safety, environment, and users’ comfort. People’s safety was investigated in terms of the electromagnetic emissions emanating from two superfast chargers of 350 kW and 300 kW, as such high charging power during the charging process could be a risk to people’s health and electronics inside and outside the bus. The results showed that the magnetic and electrical emissions are far below the safety standard limits. This confirms that the developed vehicles and chargers in the ASSURED project operate under safe conditions for people in the vicinity of the charging station. Environmental impact and users’ comfort were studied in terms of electric motor noises (compared to diesel engines), power electronic devices and their cooling, contact noises of the pantograph, and vibration inside the BEBs compared to diesel buses. It was found that, in most cases, the outside noise emission of BEBs are significantly lower than the noise emissions emitted by diesel buses. Considering the inside noise emissions in the passenger’s section, all BEBs showed lower Sound Pressure Levels (SPLs) in comparison to the diesel busses. As a second part of the ride comfort, vibrations inside BEBs are on the same level as some diesel buses but are mostly significantly lower. All charging processes (pantograph operation and charging process) have a slight noise emission, with 64.6 dB(A) and 52.3 dB(A), respectively, when comparing the engine noise at the departure of the tested diesel buses with 70.8 dB(A) to 80.4 dB(A). Overall, a reduction in noise emissions and an improvement in the ride comfort were observed for the BEBs compared to diesel busses. The objective of this brief study is to provide bus operators, decision-makers, urban planners, and authorities with an overview of the benefits of BEBs for cities and to help them understand the various infrastructural impacts on urban areas and improve the quality of services.